2011
DOI: 10.1002/cbic.201100478
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Mode of Cladocoran A to the Human Group IIA Phospholipase A2

Abstract: The molecular basis for human group IIA phospholipase A(2) inactivation by the marine natural product cladocoran A (CLD A) has been studied in order to elucidate its relevant anti-inflammatory properties. Indeed, secretory phospholipases A(2) are well-known to be implicated in the pathogenesis of inflammation, such as rheumatoid arthritis, septic shock, psoriasis and asthma, thus the understanding of their inactivation mechanism could be useful for the development of new chemical classes of selective inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…As in our previous studies, in which both bee venom and human synovial PLA 2 were shown to be affected by covalent and noncovalent interactions with bioactive natural inhibitors, [20][21][22][23][24] we applied a mass spectrometric approach in the analysis of the sPLA 2 -IIA-SLD adduct. First, we used of p-nitrophenacyl bromide (pNBr, M W 244 Da), a well-known specific ligand of the His47 of several PLA 2 s, the residue acting as Brønsted base in the catalytic process.…”
Section: Analysis Of the Spla 2 -Iia-sld Complex By Mass Spectrometrymentioning
confidence: 99%
See 4 more Smart Citations
“…As in our previous studies, in which both bee venom and human synovial PLA 2 were shown to be affected by covalent and noncovalent interactions with bioactive natural inhibitors, [20][21][22][23][24] we applied a mass spectrometric approach in the analysis of the sPLA 2 -IIA-SLD adduct. First, we used of p-nitrophenacyl bromide (pNBr, M W 244 Da), a well-known specific ligand of the His47 of several PLA 2 s, the residue acting as Brønsted base in the catalytic process.…”
Section: Analysis Of the Spla 2 -Iia-sld Complex By Mass Spectrometrymentioning
confidence: 99%
“…First, we used of p-nitrophenacyl bromide (pNBr, M W 244 Da), a well-known specific ligand of the His47 of several PLA 2 s, the residue acting as Brønsted base in the catalytic process. [20][21][22][23][24] Comparative pNBr modification experiments in the presence and absence of a given inhibitor provide valuable evidence on the type of inhibition mechanism (whether competitive or not). Therefore, we incubated sPLA 2 -IIA with pNBr, and the mixture was monitored by LC-ESI-MS.…”
Section: Analysis Of the Spla 2 -Iia-sld Complex By Mass Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations